The Role of Bissu in the Maggiri Ceremony for the Community in Segeri District (A Historical-Sociological Study) - Syarifah Nafisah; Nur Hayati; ST Haniah (Universitas Muhammadiyah Palu, 2026)
This study examines the role of Bissu in the Maggiri ceremony in the Bugis community in Segeri District. There were three themes of discussion, namely: First, the background of the emergence of the Bissu community in Segeri District, second, the urgency of the maggiri ceremony for the Segeri community, third, the values contained in the maggiri ritual ceremony. This research is a literature study by taking a historical and sociological approach to uncover the role of the Bissu sentar in the maggir event in Segeri. The study examines the ritual function, communication structure, and social dynamics surrounding Maggiri practice.The findings show that Bissu acts as a mediator between humans and the ancestral world, the leader of purification rites, a symbolic determinant of the time of execution, and the custodian of spiritual values and the sustainability of tradition. This role is manifested through a series of sacred acts such as mantras, Maggiri dances, and the purification procession of heirlooms (sere), which strengthen social cohesion and Bugis cultural identity. However, the study also found a decline in the number of Bissu and a change in function due to the process of modernization, Islamization, and economic pressure—which had an impact on the reduction of sacred authority and the transformation of ritual practices towards cultural adaptation and tourism. The research emphasizes the importance of preservation efforts that are sensitive to local values, including documentation support, cultural education, and participatory policies involving the Bissu community to keep Maggiri traditions meaningful for future generations.